Real-World Clinical Outcomes of Ujvira® (Trastuzumab Emtansine Biosimilar) in HER2-Positive Breast Cancer: A Retrospective Observational Study in Indian Patients (Journal of Cancer Research Updates, 2025)
Background: HER2-positive breast cancer is an aggressive subtype requiring targeted therapies. Trastuzumabemtansine has shown efficacy in clinical trials but remains costly, limiting accessibility in low-resource settings. Ujvira®, a biosimilar of T-DM1, offers a more affordable alternative. This study evaluates its real-world efficacy and safety in Indian patients.Methods: This is a retrospective analysis of HER2-positive breast cancer patients treated with Ujvira® between January 2022 and December 2023 at a tertiary care center in India. Primary endpoint was progression-free survival (PFS). Secondary endpoints included overall survival (OS), safety and clinical response per RECIST v1.1. Kaplan-Meier analysis was used for survival estimates; comparisons across lines of therapy were assessed using the log-rank test.Results: The study included 23 patients (median age 51 years, range 35–72), with 74% having an ECOG performance status of 0–1. T-DM1 biosimilar was administered in a palliative setting to 20 patients and as adjuvant therapy to 3 patients. Among the palliative group, 45% had brain metastases at baseline, and treatment was given as second-line in 45%, third-line in 40%, and fourth-line or later in 15% of cases. Overall, 50% achieved a partial response, 35% had stable disease, and 15% showed disease progression. At a median follow-up of 15 months, 30% remained on treatment, 65% had progressed, and one patient was lost to follow-up. The median PFS was 9.6 months, and the median OS was 14 months. In the adjuvant setting, 2 of 3 patients completed 14 cycles, while one progressed with brain metastases after 9 cycles. The most common adverse events were thrombocytopenia, anemia, and transaminitis, with grade 3 events occurring in 26% and grade 4 events in 4% of patients.Conclusion: Ujvira® showed efficacy comparable to innovator T-DM1 in terms of PFS, supporting its role in HER2-positive breast cancer management. However, shorter OS may reflect high brain metastases rates and limited access to post-progression therapies. The study’s retrospective design, small sample size, and selection bias limit generalizability. Larger prospective studies are needed to validate findings.